KACAPI DALAM TEMBANG SUNDA CIANJURAN: KETERKAITANNYA DENGAN GAMELAN DEGUNG - Nugraha, Asep (Paraguna, 2017)
Kacapi in tembang sunda cianjuran  related  to gamelan degung.  Bonang melodies in  gamelan  degung  were   adopted  by  Kacapi  Indung,  and  peking  melodies   in gamelan degung   were  adopted  by  kacapi rincik.  This paper tries  to explore the relationship  by  comparing the  melodic  between the  kacapi instruments  and  the instruments in the  gamelan gamelan degung.  The  result was   kacapi in tembang sunda cianjuran  as miniature of the gamelan degung performance.